(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Over the centuries, the Islamic religion, Sufism, manifestations of Sufis and their teachings appeared and developed in our land. That we are the owner of a huge heritage of Sufism and Sufism through the material, manuscript and word-of-mouth masterpieces that exist in Central Asia, and that we have proves that it has made strong progress. Today, Uzbekistan is a leading country in Central Asia, whose history and culture are deeply analyzed through material and spiritual sources of real historical value and significance, and in terms of the quantity and uniqueness of epigraphic monuments. But most of them have not been studied before.